A comprehensive indoor hygiene concept for infection prevention and control within built environments - Salonen Noora; Mäkinen Riika; Ahonen Merja; Mäkitalo Tiina; Pelto-Huikko Aino; Latva Martti (Frontiers Media S.A., 2025)
The COVID-19 pandemic has shown that actions related to infection prevention and control (IPC) need to be made more efficient, especially in indoor public spaces. Many standalone technologies and solutions are available to increase the hygiene levels of indoor environments. However, it is not clear how these technologies and solutions can be combined and adapted to building processes such that they cover the entire indoor environment and life cycle of a building-from its design to its use and maintenance. The construction industry faces challenges in this regard because many actors are involved, and interactions at multiple levels can hinder the implementation of innovations. Therefore, the aim of this article is to establish a framework for IPC within built environments by introducing a new indoor hygiene concept (IHC). It provides a tool for implementing necessary IPC actions during a building's life cycle to construct or renovate hygienic indoor environments. The IHC is based on the idea that all the elements of an indoor environment need to be considered to create a hygienic building. In addition, hygiene objectives need to be set at an early stage of the construction process and monitored throughout all the phases of a building's life cycle. This comprehensive approach enables designers, engineers, and other actors involved in different stages of a building's life cycle to see their roles in the IPC of shared public spaces. Adopting this approach can result in fewer infection transmissions via indoor environments and, in turn, cost benefits for society.